The Influence of Interactive and Integrative Learning on Active Participation of Students - Nur Hasanah Ismatullah; Nuur Alfi Laelah; Siti Ramina Agustina (Jurnal At-Tadbir : Media Hukum dan Pendidikan, 2026)
Low levels of students' active participation in Islamic Religious Education (IRE) learning are often attributed to monotonous and less engaging instructional methods. This study aimed to examine the effects of interactive and integratif learning on students' active participation at SMPN 1 Sukalarang, Sukabumi Regency. The study employed a quantitative approach using a survey method. Data were collected through questionnaires administered to 45 students and analyzed using multiple regression to examine the effects of the two independent variables on the dependent variable. The findings revealed that interactive learning had a positive and statistically significant effect on students' active participation, with a t-value of 6.118 and a significance level of 0.000. Similarly, integratif learning demonstrated a positive and significant effect, with a t-value of 4.418 and a significance level of 0.000. Furthermore, the multiple regression analysis indicated that the combined effects of interactive and integratif learning could explain 75.7% of the variance in students' active participation. The study concludes that the simultaneous implementation of interactive and integratif learning significantly enhances students' active participation in Islamic Religious Education classes. Therefore, teachers are encouraged to integrate both instructional approaches to create a more engaging, meaningful, and effective learning environment.